BANYUWANGI REBOUND: REBRANDING NILAI BATIK BANYUWANGI SEBAGAI UPAYA EDUKASI KEARIFAN LOKAL DAN STRATEGI PENINGKATAN PENJUALAN BATIK PASCA PANDEMI COVID-19 - Rosyidah, Elok (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Banyuwangi Rebound is one of the superior work programs of the Banyuwangi Regency Government in the process of recovering the economic sector. The art of batik in Indonesia has been known since the days of the Majapahit kingdom and continues to grow until the next kingdom and its kings. Batik is generally widespread in Indonesia and particularly in Java after the 18th century or early 19th century (Akhmad, 2016: 3). Banyuwangi in an effort to preserve and introduce Banyuwangi batik by holding the Banyuwangi Batik Festival (BBF) every year. The theme of the different BBF events each year gives a special impression to the visitors. The method used in this research is descriptive qualitative. The process of establishing the rebranding of Banyuwangi batik values ​​as an effort to educate local wisdom and increase sales of Batik in Banyuwangi requires the formulation of strategies that are right on target so that it can be realized. The realization of shared ideals related to preserving the value of batik through education of batik local wisdom and increasing sales of Batik in Banyuwangi can be achieved through strategic steps with a spirit of togetherness and collective awareness.